Efficacy of mouthrinse spray in inhibiting cariogenic biofilm formation on toothbrush bristles - Andresa Piacezzi Nascimento; Gisele Faria; Evandro Watanabe; Izabel Yoko Ito (Universidade Estadual de Campinas, 2016)
Aim: The aim of this study was to evaluate the efficacy of Periogard® (Colgate-Palmolive) and Plax® (Colgate-Palmolive) in inhibiting biofilm formation of mutans streptococci (MS) on toothbrush bristles used just once for 2 minutes with no dentifrice. Methods: This study was performed into 3 phases in which mouthrinses and sterile distilled water (control group) were sprayed 6 times (to standardize the method) on toothbrush bristles used by 53 university students. Toothbrushes were kept at room temperature for 3 hours and put into test tubes each containing bacitracin sucrose broth (selective enrichment for MS). After incubation at 37ºC for 3 to 4 days, MS biofilm on the bristles were analyzed and colony-forming units (CFU) were counted by stereomicroscope under reflected light. Results: 41 students completed the 3 phases of this study and 38 (92.7%) control group toothbrushes had CFU of MS that varied from 1 to uncountable. Periogard® and Plax® inhibited biofilm formation on the bristles of 97.4% and 84.2% toothbrushes, respectively. Conclusion: Periogard® and Plax®, in spray, reduced/eliminated biofilm formation of MS on the toothbrush bristles. However, Periogard® was more efficacious than Plax® for this purpose.